Local Legumes from Dry Land of East Nusa Tenggara: Diversity, Nutritional Composition, and Their Use in Society – A Literature Study - Hyldegardis Naisali; Jatmiko Eko Witoyo; Panggulu Ahmad Ramadhani Utoro (JITIPARI, 2023)
East Nusa Tenggara (ENT) is a province in Indonesia with diverse flora, including the diversity of local legumes. It has been extensively explored and reported in various scientific publications, especially the types of legumes, their nutritional composition, and their uses in local communities. However, few literature studies still comprehensively review the types of legumes, their nutritional composition, and their utilization in the local community of ENT. So, this literature review aims to briefly review the diversity, chemical composition, and use of local legumes from the dry lands of ENT. Various studies reported that Glycine max, Arachis hypogaea, Vigna radiata (L.) R. Wilczek, Cajanus cajan, Vigna unguiculata, Phaseolus lunatus, Vigna umbellata, Lablab purpureus (L.) Sweet, Mucuna pruriens (L.) DC, Phaseolus vulgaris L, Psopocarpus tetragonolobus (L.) DC, and Pueraria montana var. lobata (Willd.) Sanjappa & Pradeep nuts are commonly found in the ENT region, either cultivated by the local community or grown wild. Generally, local legumes in ENT have a relatively complete nutritional composition, which varies depending on the type of bean. The ENT's local people use local beans as a mixture of rice/corn and function as sources of protein. Future research is needed to explore the functional characteristics of each ENT local bean. In addition, it is necessary to develop formulations and other food products to utilize ENT's local legumes to diversify legume-based local food.